Is Health Literacy of Dialyzed Patients Related to Their Adherence to Dietary and Fluid Intake Recommendations? - Skoumalova, Ivana; Kolarcik, Peter; Madarasova Geckova, Andrea; Rosenberger, Jaroslav; Majernikova, Maria; Klein, Daniel; van Dijk, Jitse P; Reijneveld, Sijmen A (International journal of environmental research and public health, 2019)
Non-adherence to dietary and fluid intake recommendations (NADFIR) is an important factor for the effective treatment of dialyzed patients and may be hindered by low health literacy (HL). Therefore, we assessed whether low HL of dialyzed patients is associated with their NADFIR. We performed a multicentric cross-sectional study in 20 dialysis clinics in Slovakia (n = 452; response rate: 70.1%; mean age = 63.6 years; males: 60.7%). We assessed the association between nine domains of HL and non-adherence (high serum potassium, high serum phosphate, relative overhydration, and self-reported NADFIR) using general linear models adjusted for age and gender. Moreover, we assessed the moderation by socioeconomic status (SES). We found higher NADFIR among patients with less sufficient information for health management (high serum phosphate level; odds ratio (OR): 0.77; 95% confidence interval (CI): 0.63-0.94), with a lower ability to actively manage their health (self-reported diet non-adherence; OR: 0.74; 95% CI: 0.62-0.89), and those less able to actively engage with healthcare providers (overhydrated; OR: 0.78; 95% CI: 0.65-0.94). Moreover, SES modified this relation. Low HL affects the adherence of dialyzed patients. This shows a need to support patients with low HL and to train healthcare providers to work with these patients, taking into account their SES.
Keywords: Humans; přijímání potravy; lidé středního věku; zpráva o sobě; Diet; Eating; Self Report; Renal Dialysis; Female; Aged; mladý dospělý; dospělí; Patient Compliance; dialýza ledvin; senioři; lidé; zdravotní gramotnost; Health Literacy; Slovenská republika; Slovakia; pití; Adult; společenská třída; fluid intake adherence; ženské pohlaví; Male; Middle Aged; dieta; Aged, 80 and over; diet adherence; Cross-Sectional Studies; Young Adult; senioři nad 80 let; Drinking; Social Class; health literacy; mužské pohlaví; dialyzed patients; adherence pacienta; non-adherence; průřezové studie